2008
DOI: 10.1155/2008/727505
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns in Invasive Group B Streptococcal Isolates

Abstract: Antibiotics are used for both group B streptococcal (GBS) prevention and treatment. Active population-based surveillance for invasive GBS disease was conducted in four states during 1996–2003. Of 3813 case-isolates, 91.0% (3471) were serotyped, 77.1% (2937) had susceptibility testing, and 46.6% (3471) had both. All were sensitive to penicillin, ampicillin, cefazolin, cefotaxime, and vancomycin. Clindamycin and erythromycin resistance was 12.7% and 25.6%, respectively, and associated with serotype V (P < .001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 13 publications
7
73
2
2
Order By: Relevance
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 76%
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 76%
“…As serotype V GBS isolates have become the predominant GBS serotype causing invasive infections in adult patients and neonates in the USA and Canada (Castor et al, 2008;Dogan et al, 2005), Australia and New Zealand (Zhao et al, 2008), the predominance of serotype V among Kuwaiti women may be considered an emerging public health concern. Curiously, our results differed from those reported for pregnant women in neighbouring countries such as the United Arab Emirates, where serotype IV (26.3 %) was the most common serotype among GBS isolates (Amin et al, 2002), or Iran, where serotype III (41.8 %) was the most common serotype (Mansouri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological study of GBS serotypes is important because the GBS serotype is associated with pathogenicity (10,12,14) and antibiotic susceptibility (10)(11)(12)22). In addition, the development and formulation of current multivalent GBS vaccines depends on accurate population data of the serotype distribution (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alternative antibiotics are administrated for pregnant women with penicillin allergy, such as clindamycin, erythromycin, cefazolin, or vancomycin. In several countries, both clindamycin and erythromycin resistance has been reported in GBS isolates (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation